Environmental Factors Variably Impact Tea Secondary Metabolites in the Context of Climate Change - Ahmed, Selena; Griffin, Timothy S.; Kraner, Debra; Schaffner, M. Katherine; Sharma, Deepak; Hazel, Matthew; Leitch, Alicia R.; Orians, Colin M.; Han, Wenyan; Stepp, John Richard; Robbat, Albert; Matyas, Corene; et al. (Frontiers in Plant Science, 2019)
Climate change is impacting food and beverage crops around the world with implications for environmental and human well-being. While numerous studies have examined climate change effects on crop yields, relatively few studies have examined effects on crop quality (concentrations of nutrients, minerals, and secondary metabolites). This review article employs a culturally relevant beverage crop, tea (Camelia sinensis), as a lens to examine environmental effects linked to climate change on the directionality of crop quality. Our systematic review identified 86 articles as relevant to the review question. Findings provide evidence that shifts in seasonality, water stress, geography, light factors, altitude, herbivory and microbes, temperature, and soil factors that are linked to climate change can result in both increases and decreases up to 50% in secondary metabolites. A gap was found regarding evidence on the direct effects of carbon dioxide on tea quality, highlighting a critical research area for future study. While this systematic review provides evidence that multiple environmental parameters are impacting tea quality, the directionality and magnitude of these impacts is not clear with contradictory evidence between studies likely due to confounding factors including variation in tea variety, cultivar, specific environmental and agricultural management conditions, and differences in research methods. The environmental factors with the most consistent evidence in this systematic review were seasonality and water stress with 14 out of 18 studies (78%) demonstrating a decrease in concentrations of phenolic compounds or their bioactivity with a seasonal shift from the spring and /or first tea harvest to other seasons and seven out of 10 studies (70%) showing an increase in levels of phenolic compounds or their bioactivity with drought stress. Herbivory and soil fertility were two of the variables that showed the greatest contradictory evidence on tea quality. Both herbivory and soil fertility are variables which farmers have the greatest control over, pointing to the importance of agricultural management for climate mitigation and adaptation. The development of evidence-based management strategies and crop breeding programs for resilient cultivars are called for to mitigate climate impacts on crop quality and overall risk in agricultural and food systems.